Innovation Networks in Different Industrial Settings: From Flexible to Smart Specialization - Håkan Ylinenpää; Jukka Teräs; Daniel Örtqvist (European Journal of Spatial Development, 2016)
The key research objective of this paper is to analyse industrial specialisation by developing innovative networks linked to the region. Institutional and entrepreneurial innovation systems, smart specialisation and a network based research framework for entrepreneurship are used as conceptual foundations in the paper. Based on theoretical elaborations our analyses illustrate how certain interventions have stimulated regional development and innovation in two specific Scandinavian regions. Our results highlight that both regions have gone from interventions fostering flexible specialization, with the motive of staying resilient and competitive over time, to an approach based on smart specialization with a focus on one or a limited number of strong industries.